2017
DOI: 10.1109/tasc.2016.2641341
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Test Results of Coil 2 of a Three-Coil 800-MHz REBCO Insert for the 1.3-GHz High-Resolution NMR Magnet

Abstract: This paper focuses on the construction and test results of Coil 2 that is part of a trio of nested coils composing the REBCO 800 MHz insert. Upon its completion, the REBCO 800 MHz insert will be placed in the bore of a 500 MHz low temperature superconducting (LTS) NMR magnet (L500) to form the MIT 1.3 GHz high-resolution NMR magnet. Coil 2 is a stack of 32 double pancake (DP) coils wound with 6-mm wide REBCO tape using the no-insulation (NI) technique. Each pancake is wound on a stainless steel inner supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In previous calculations, Zhang et al have also derived the non-uniform ρ t2t distribution that innermost and outermost turns have the largest ρ t2t values for an NI coil wound with a uniform pre-stress of 25 MPa [63]. Similar calculations in [64][65][66][67] have demonstrated that the innermost and outermost turns of the HTS coil theoretically have the minimum radial stress, which in the NI coil would result in the larger ρ t2t value on these turns [63]. In this work, the non-uniform ρ t2t distribution might come from; (i) the innermost and outermost turns of the HTS coil naturally have the minimum radial stress [63][64][65][66][67]; (ii) 50 Hz AC field induced Lorentz force vibrations on HTS tapes, making the winding flexible thus more liquid nitrogen penetration in the turn-to-turn intervals, especially for the inner/outermost several turns.…”
Section: Simulation Analysismentioning
confidence: 87%
“…In previous calculations, Zhang et al have also derived the non-uniform ρ t2t distribution that innermost and outermost turns have the largest ρ t2t values for an NI coil wound with a uniform pre-stress of 25 MPa [63]. Similar calculations in [64][65][66][67] have demonstrated that the innermost and outermost turns of the HTS coil theoretically have the minimum radial stress, which in the NI coil would result in the larger ρ t2t value on these turns [63]. In this work, the non-uniform ρ t2t distribution might come from; (i) the innermost and outermost turns of the HTS coil naturally have the minimum radial stress [63][64][65][66][67]; (ii) 50 Hz AC field induced Lorentz force vibrations on HTS tapes, making the winding flexible thus more liquid nitrogen penetration in the turn-to-turn intervals, especially for the inner/outermost several turns.…”
Section: Simulation Analysismentioning
confidence: 87%
“…Coils 2 and 3 were wound with a winding tension of 50 N. Wound with the no-insulation technique as was Coil 1, they are also compact, self-protecting, and with high mechanical robustness. Another feature, first applied to Coil 1 is the inclusion of a 1-mm thick inner stainless steel ring to prevent collapsing of the DP innermost turns, induced by the external pressure build up due to the winding tension [4].…”
Section: Coil 2: Fabrication Processesmentioning
confidence: 99%
“…Fig. 1 shows the general arrangement of our PCS coil, which was assembled using a spare NI DP remaining after fabrication of Coil 2 of our 800-MHz REBCO insert for a 1.3-GHz spectrometer magnet [17]. Nominal conductor and coil characteristics are summarized in [17].…”
Section: Pcs Coil Configurationmentioning
confidence: 99%